2007
DOI: 10.1038/sj.gt.3302966
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antileukemia effect of combinational gene therapy using murine b-defensin 2 and IL-18 in L1210 murine leukemia model

Abstract: Murine b-defensin 2 (MBD2) is not only chemotactic for immature dendritic cells but also activates them by Toll-like receptor 4. We have previously demonstrated that vaccine with MBD2 elicited potent antileukemia responses in the L1210 murine model. Interleukin-18 (IL-18) is an essential cytokine for the generation of Th1 response and natural killer cells and cytotoxic T lymphocytes (CTL) activation. As MBD2 and IL-18 appear to function on different components required by an effective antitumor immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…IFN-γ is predominately secreted by activated Th1, CD8 + T cells, and NK cells while IL-12 is produced by activated antigen presenting cells. Conceivably, vaccination with B16-mBD2 induces pro-inflammatory Th1, CD8 + T cells, and activates NK cells, consistent with previous findings [11], [17]. As a result, the activated immunocompetent cells may migrate into the tumor tissues, inhibiting the growth of implanted melanoma in mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IFN-γ is predominately secreted by activated Th1, CD8 + T cells, and NK cells while IL-12 is produced by activated antigen presenting cells. Conceivably, vaccination with B16-mBD2 induces pro-inflammatory Th1, CD8 + T cells, and activates NK cells, consistent with previous findings [11], [17]. As a result, the activated immunocompetent cells may migrate into the tumor tissues, inhibiting the growth of implanted melanoma in mice.…”
Section: Discussionsupporting
confidence: 90%
“…β-defensin 2 is an antimicrobial peptide and can regulate immune response [8]. Previous studies have shown that vaccination with plasmids for the fused protein of β-defensin 2 and tumor antigen or with β-defensin 2-expressing irradiated tumor cells stimulates strong antitumor immune responses against lymphoma, leukemia, and mammary adenocarcinoma in vivo [10], [11], [17], [18]. In this study, we determined whether β-defensin 2 could act as an adjuvant to induce melanoma-specific T cell immunity in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-18 enhances the efficacy of DNA vaccines directed against prostate-specific antigen [14] or Fos-related antigen [15]. Additionally, IL-18 augments the efficacy of DC-based vaccines [16], [17] as well as whole-cell tumor vaccines [18]. However, IL-18 has also been reported to enhance tumor progression (reviewed in [19]).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the immunomodulatory of inflammasome activities, particularly IL-18, can be harnessed for immunotherapy against cancer. IL-18 has been shown to play an important role in the induction of IFNγ production, increasing NK cell activity and T cell proliferation ( 135 140 ). Notably, those immunoregulatory activities of IL-18 are overlapped with that of IL-12.…”
Section: Introductionmentioning
confidence: 99%